The Interconnectedness of Indigenous Religion and Indigenous Territory: A Case Study of Talang Mamak, Riau - Muntaza Muntaza (Umbara, 2022)
The Constitutional Court Decision 97/2016 emphasizes Bhinneka Tunggal Ika which is the diversity of Indonesia and observed to be another path to rebuild the relationship between the state and the indigenous people, especially concerning the citizenship framework. However, that decision is not enough to guarantee the sustainable reproduction of indigenous people’s religion. This research aimed to showed an interconnection between Indigenous religion and indigenous territory among Talang Mamak people in Riau Province. This research was conducted using qualitative method. There is possibility of tracing the interaction to nature and this implies it is not only a means of subsistence but also has both horizontal and vertical meanings embedded in their indigenous religion narrative. This relationship represents their strong emotional and spiritual connection to nature as well as the foundation to build their identity and form their worldview.